DAMPAK PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) MELALUI APLIKASI GOOGLE MEET TERHADAP HASIL BELAJAR PESERTA DIDIK - Radimin, Poetry Fahruddin; Suarman, Suarman; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine whether there is an impact of implementing the TPS (Think Pair Share) type of cooperative learning model through the Google Meet application on student learning outcomes. This type of research is experimental research. The population of this study was the grade VIII students of SMP Negeri 2 Pangkalan Kerinci in the academic year 2020/2021, totaling 174 students. The sampling technique was using purposive sampling technique. Data collection techniques used tests and data analysis techniques used data analysis using independent samples t test. The result of this research is the TPS (Think Pair Share) cooperative learning model through the google meet application can provide a significant increase in student learning outcomes. The suggestion of this research is that in applying the cooperative learning model type TPS (Think Pair Share) through the google meet application on social studies subjects can improve learning outcomes of students and in the division of discussion groups teachers should pay attention to the level of ability of students so that in one group each member can help each other share understanding.Key Words: TPS (Think Pair Share), Google Meet, Learning Outcomes